Partial thickness subfoveal hole in a patient treated with tamoxifen: a case report and review of the literature - Ashley Sohn; George Sanchez; Dimosthenis Mantopoulos (Journal of Medical Case Reports, 2022)
Abstract Background We describe a patient presenting with a partial thickness subfoveal hole in the right eye after tamoxifen treatment for breast cancer. Case presentation A 76-year-old Caucasian female presented with a 1-day history of acute central scotoma and blurry vision in the right eye. The patient had been receiving oral tamoxifen for 5 years as adjuvant treatment for stage I lobular breast cancer. Her past ocular history was significant for complete, uneventful, and bilateral posterior vitreous detachment. Clinical examination and optical coherence tomography revealed a new, partial thickness subfoveal hole sparing the inner retinal layers. Observation was recommended. At the last follow-up examination, 1 year after the initial presentation, the subfoveal hole remained stable and visual acuity remained stable. Conclusion Tamoxifen has been associated with a plethora of ophthalmic adverse events, including macular holes, some of which are partial thickness subfoveal holes. Holes with this almost unique morphology are uncommon, and eye care professionals should be aware of this association given the frequency of tamoxifen use, as well as the low success rate of surgical repair with pars plana vitrectomy.